Biotic and Abiotic Drivers of Ecosystem Temporal Stability in Herbaceous Wetlands in China - Guodong Wang; Nanlin Hu; Yann Hautier; Beth Middleton; Ming Wang; Meiling Zhao; Jingci Meng; Zijun Ma; Bo Liu; Yanjie Liu; Ming Jiang (Global Change Biology, 2025)
Maintaining the stability of ecosystems is critical for supporting essential ecosystem services over time. However, our understanding of the contribution of the diverse biotic and abiotic factors to this stability in wetlands remains limited. Here, we combined data from a field vegetation survey of 725 herbaceous wetland sites in China with remote sensing information from the Enhanced Vegetation Index (EVI) from 2010 to 2020 to explore the contribution of biotic and abiotic factors to the temporal stability of primary productivity. We found that plant species richness directly contributed to stability on a national scale, but that this contribution differed among climate zones, hydrological regimes, and vegetation types. In addition, many abiotic factors, including soil properties, geographical location, and climate also contributed to stability. Piecewise structural equation modeling identified that soil properties, including soil pH, total nitrogen, and soil organic carbon, emerged as primary factors modulating ecosystem stability, both directly and indirectly by affecting species richness and vegetation type. Higher species richness and soil organic carbon were related to higher ecosystem stability in peatlands but less so in coastal and inland marshes. These findings enhance our ability to forecast how wetland ecosystems may respond to future environmental changes and biodiversity loss and can inform policy decisions related to ecosystem stability.